Functionalized Nanoporous Track-Etched b-PVDF Membrane Electrodes for Heavy Metal Determination by Square-Wave Anodic Stripping Voltammetry - Bessbousse H.; Barsbay M.; Güven O.; Clochard M.-C.; Wade T. L. (E3S Web of Conferences, 2013)
Track-etched functionalized nanoporous β-PVDF membrane electrodes, or functionalized membrane electrodes (FMEs), are electrodes made from track-etched, poly(acrylic acid) (PAA) functionalized nanoporous β-poly(vinylidene fluoride) (β-PVDF) membranes with thin porous Au films sputtered on each side as electrodes. To form the β-PVDF nanoporous membranes, β-PVDF films are irradiated by swift heavy ions. After irradiation, radical tracks are stable in the membranes. Chemical etching removes some of the radical tracks revealing nanopores. Radicals, remaining in the pores, initiate radio grafting of PAA from the pore walls of the nanoporous β-PVDF. PAA is a cation exchange polymer that adsorbs metal ions, such as Pb2+, from aqueous solutions thus concentrating the ions into the membrane. After a calibrated time the FME is transferred to an electrochemical cell for square-wave anodic stripping voltammetry analysis.